G98(P) Demystifying the 'paediatric assessment'. (May 2019) - Fautz, T; Fuller, H; Taylor, A; Ayadi O'Donnell, N; Potter, M; Hodes, D
Abstract : Objectives: There is a common misconception that the 'Paediatric Assessment' (PA) following an allegation of child sexual abuse (CSA) is distressing and abusive. Our specifically designed teaching package set out to dispel this myth and provide multi-disciplinary training on what a PA consists of. A rapid 'Plan, Do, Study, Act' (PDSA) cycle was performed to improve training material. Method: A teaching package and a 37 question pre- and post-training questionnaire were delivered at five teaching sessions. 95 participants attended the multi-disciplinary meetings. The questionnaires were used to gather feedback and amend the teaching package accordingly. Results: We did not find any difference in responses between participants working for different sectors, nor between participants with different levels of experience managing cases of alleged sexual abuse. Our teaching package gave participants a greater understanding of the PA and our child centred holistic approach. The number of participants who thought a medical history is always taken prior to examination doubled (43.2% to 85.3%), and fewer thought that children experience distress from an examination of their private parts (53.7% to 21.1%). Initially only 11 participants (11.6%) felt definitely able to explain what happens in a PA compared with 66 participants (69.5%) afterwards. After teaching a greater number of participants felt the PA is useful for: providing reassurance to the child and their parents/carers; considering other forms of abuse; and considering the impact on the child's education, development, behaviour and emotions. Before training 31.6% of participants would have been deterred from referring for a PA if a child alleged touching but no penetration. After training this number fell to 16.8%. 86.3% of participants felt that the questionnaires enhanced their learning experience. Conclusions: Our teaching package increased participants' knowledge about what a PA involves, and we dispelled the myth that the PA following an allegation of CSA is abusive to children. As a result participants would be more likely to refer all suspected cases of CSA in the future. Using a PDSA methodology and questionnaire facilitated more focused teaching and learning.